Mrhapharli Thakali Samaj - Aryal, Sabitri (Tribhuvan University Journal, 2010)
Not available.Key words: Thakali Samaj; Thakkhola; Mustang; NepalTribhuvan University Journal Volume XVI, 1993Page:108-113Uploaded date: 4 October, 2010